2003
DOI: 10.1097/00004872-200306000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycaemic control on the vascular nitric oxide system in patients with type 1 diabetes

Abstract: In patients with diabetes type 1, glycaemic control determines the functioning of the NO system by a reversible mechanism involving superoxide anions. This finding provides an explanation of the relationship between glycaemic control and vascular complications in diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…None of these studies revealed abnormal responses to endothelium-independent vasodilators; in contrast, another study [67] demonstrated preserved responses to acetylcholine, but a reduced response to nitroprusside and a reduced effect of L-NMMA on basal blood flow, suggesting decreased basal release of nitric oxide. A blunted constrictor response to L-NMMA in patients with poorly controlled diabetes has also been described [64]. A blunted constrictor response to L-NMMA in patients with poorly controlled diabetes has also been described [64].…”
Section: Type 1 Diabetesmentioning
confidence: 96%
See 1 more Smart Citation
“…None of these studies revealed abnormal responses to endothelium-independent vasodilators; in contrast, another study [67] demonstrated preserved responses to acetylcholine, but a reduced response to nitroprusside and a reduced effect of L-NMMA on basal blood flow, suggesting decreased basal release of nitric oxide. A blunted constrictor response to L-NMMA in patients with poorly controlled diabetes has also been described [64]. A blunted constrictor response to L-NMMA in patients with poorly controlled diabetes has also been described [64].…”
Section: Type 1 Diabetesmentioning
confidence: 96%
“…The data concerning endothelial function in type 1 (insulin-dependent) diabetes mellitus are conflicting, although a number of investigators have demonstrated forearm endothelial dysfunction [58][59][60][61][62][63][64]. In most studies, responses to endothelium-independent agonists were preserved, indicating decreased nitric oxide bioactivity.…”
Section: Type 1 Diabetesmentioning
confidence: 99%
“…A pro-oxidant and pro-inflammatory vascular environment is another characteristic of endothelial dysfunction (Félétou and Vanhoutte, 2006). Endothelial dysfunction is linked to the early development of DM in both humans and experimental animal models, and associated to reactive oxygen species (ROS) over-production (Durante et al, 1988; Calver et al, 1992; Johnstone et al, 1993; Angulo et al, 1998; Rodríguez-Mañas et al, 2003a,b). …”
Section: Il-1β Blockade and Experimental Diabetic Vasculopathymentioning
confidence: 99%
“…Produced by NO synthase from substrate L-arginine in vascular endothelial cells, NO acts as a potent vasodilator contributing to the regulation of vascular tone. [16][17][18] In the uremic condition, endothelial dysfunction and reduced production and effect of NO have been observed.…”
Section: Endothelin-1 and Nitric Oxide In Patients On Hemodialysismentioning
confidence: 99%